2020
DOI: 10.1177/0194599820931486
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Balloon Dilation in Treatment of Subglottic Stenosis With a Rabbit Model

Abstract: Objectives Identify the effects of balloon dilation duration and topical ciprofloxacin-dexamethasone application in treatment of subglottic stenosis. Study Design Randomized controlled trial. Setting Animal research facility. Subjects and Methods Forty-four rabbits underwent subglottic injury in an Institutional Animal Care and Use Committee–approved study. One week after injury, the subglottis of each rabbit was measured and treated with endoscopic balloon dilation for 2 rounds of short duration (SBD; 3 secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…We expect that a better effect will be achieved with long dilatation based on many years of experience with 10‐minute dilatation tracheoscopy using the Groningen Dilatation Tracheoscope (Karl Storz) 2 . Additionally, a recent study in rabbits, showed significantly more effect after long dilatation when compared to short dilatation 4 . In current studies, however, the duration of balloon dilation in humans varies widely and further research is required to confirm the optimal time of dilatation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We expect that a better effect will be achieved with long dilatation based on many years of experience with 10‐minute dilatation tracheoscopy using the Groningen Dilatation Tracheoscope (Karl Storz) 2 . Additionally, a recent study in rabbits, showed significantly more effect after long dilatation when compared to short dilatation 4 . In current studies, however, the duration of balloon dilation in humans varies widely and further research is required to confirm the optimal time of dilatation.…”
Section: Discussionmentioning
confidence: 92%
“…With the conventional balloon dilatation, the airway is blocked, hence only allowing for intermitted dilatation for approximately 30–60 s each time avoiding patient hypoxemia 3 . A recent study in rabbits, showed significantly more effect after long compared to short dilatation 4 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have reported anecdotal success in reducing or resolving tracheal granulation tissue with adjunctive treatments, such as the utility of local Ciprodex (ciprofloxacin-dexamethasone). [28][29][30] It is hypothesized that the ciprofloxacin acts to decrease bacterial load and associated inflammation, while the dexamethasone acts synergistically with an anti-inflammatory effect at the sight of airway injury. [28][29][30] However, the recommendations on the utility of Ciprodex are based on anecdotal successes, still lack of quantitative data.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30] It is hypothesized that the ciprofloxacin acts to decrease bacterial load and associated inflammation, while the dexamethasone acts synergistically with an anti-inflammatory effect at the sight of airway injury. [28][29][30] However, the recommendations on the utility of Ciprodex are based on anecdotal successes, still lack of quantitative data. Thus, further research is needed to elucidate the application of Ciprodex as an effective adjuvant treatment in a quantitative manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation